Effects of Plant Density Regulation on Soil Physical Properties and Plant Diversity of Plantations in Yellow River Flood Plain of Northern Shandong Province - Wang Lichao; Xia Jiangbao; Zhao Yuyao; Chen Ping (Shuitu baochi tongbao)
[Objective] The effects of plant density regulation on soil physical properties and plant diversity of different plant stands in the Yellow River flood plain were analyzed in order to provide a theoretical basis for optimizing stand growth, improving soil physical properties, and increasing understory vegetation diversity. [Methods] Three plantations (Fraxinus chinensis, Salix matsudana, Ulmus pumila) growing under the same site conditions in the Wangzhuang Forest Farm, Lijin County, Dongying City, Shandong Province were selected as the research objects. The soil bulk density, porosity, water-holding capacity, and vegetation growth of different stand densities (3 m×3 m, 3 m×6 m) were investigated. [Results] ① Reducing stand density to 3 m×6 m increased crown width, diameter at breast height, and tree height of each stand, as well as the biomass and diversity of understory plants. The increase of each stand factor index in the U. pumila plantation was significantly greater than observed for the other stands. ② The stand density of 3 m×6 m reduced the non-capillary porosity of the same soil layer, and increased the capillary porosity and total porosity of the same soil layer. ③ The stand density of 3 m × 6 m significantly increased the saturated water-holding capacity and capillary water-holding capacity of the 0—20 cm soil layer in F. chinensis, S. matsudana, and U. pumila plantations (p<0.05), and significantly increased the soil moisture content of the 20—40 cm soil layer in the U. pumila plantation (p<0.05). [Conclusion] Decreasing stand density resulted in a significant increase in biomass and diversity of understory plants in the U. pumila plantation, and soil capillary porosity and total porosity in the F. chinensis plantation were also increased significantly. Decreasing stand density also significantly increased soil saturated water-holding capacity and capillary water-holding capacity in the 0—20 cm soil layer of F. mandshurica, U. pumila, and S. matsudana plantations, and soil water content in the 20—40 cm soil layer of the U. pumila plantation was also significantly increased.